2018
DOI: 10.5005/jp-journals-10045-0072
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Clinical Profile in Chronic Kidney Disease with Special Reference to Echo and Electrocardiography

Abstract: Introduction: Cardiovascular causes contribute toward a large proportion of increased morbidity and mortality in patients with chronic kidney disease (CKD). Cardiac disease is the major cause of death in the CKD population. Materials and methods:The present study was undertaken for documentation of various cardiovascular abnormalities in 50 patients with CKD at RajaRajeswari Medical College & Hospital, Bengaluru, Karnataka, India, using electrocardio graphy (ECG) and echocardiography as investigation proce dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Pericardial effusion and conduction abnormalities are more common in patients of CKD on haemodialysis. 13 MV Krishna, Ashish Jindal, Saurav Das in a study found that LVH is the commonest abnormality observed in CKD both on ECG and echocardiography. Echocardiography is a more sensitive diagnostic procedure to detect LVH.…”
Section: Discussionmentioning
confidence: 98%
“…Pericardial effusion and conduction abnormalities are more common in patients of CKD on haemodialysis. 13 MV Krishna, Ashish Jindal, Saurav Das in a study found that LVH is the commonest abnormality observed in CKD both on ECG and echocardiography. Echocardiography is a more sensitive diagnostic procedure to detect LVH.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, Sachdeva et al concluded that based on echocardiographic changes, LVDD was present in 38.33% patients, Krishna et al reported LVDD in 38%, Ladha et al reported LVDD in 61.4% and Singal et al reported in 50%. [22][23][24][25] Rao et al found that 67.2% of subjects had diastolic dysfunction. 26 Losi et al in a cross-sectional study declare that nearly 40% of the patients had diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%